Construção de material educativo para a avaliação da dor em recem-nascidos - Pedo, Cristiane (Universidade do Vale do Rio dos Sinos, 2019)
This is a narrative review, with the objective of analyzing the scientific production on the use of scales for pain evaluation in hospitalized newborns and produce educational material for the evaluation of newborns. Literature search was carried out in the VHL, PubMed and Scielo database over five years, with thirty-six articles selected for discussion. Evidence shows that professionals involved in the daily care of the newborn recognize that they feel pain regardless of their gestational age and that they undergo various painful procedures throughout the hospitalization period. Even recognizing pain in the newborn, few professionals use scales to measure pain. Currently not on a standard gold scale, because the numerous scales that are available, should also aim to meet each health service, its public and its main characteristics. The review found the use of pain assessment scales aimed at proving non-pharmacological and pharmacological techniques and measuring pain through a painful procedure. It was not evidencing the use of scales by health professionals in their daily life, but scales used by researchers to prove some method. A comprehensive evaluation of the newborn is necessary in a humanized, qualified and integral way, allowing decisions to be made in a cohesive way and with instruments validated and adapted to each reality. From this review it was possible to know the numerous scales available for pain measurement and to construct an educational technology aimed at nurses in the hospital area. With the possibility of measuring the pain in several procedures that will be submitted during the period of hospitalization. The use of information technology in the form of infographic aimed at nurses, contributes to reinforce its role in the humanization of care, as well as decision making in relation to the newborn exposed to pain.Key-words: Nursing. Scales. Pain measurement. Newborn.
Keywords: Enfermagem; Escalas; Avaliação da dor; Recém-nascido; Nursing; Scales; Pain measurement; Newborn; ACCNPQ::Ciências da Saúde::Enfermagem